2018
DOI: 10.1016/j.jhsa.2018.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Screw Fixation Alone for Scaphoid Fracture Nonunion

Abstract: Scaphoid fracture nonunion can often lead to pain, arthrosis, and disability. While typically the result of delayed diagnosis or inadequate treatment, it can sometimes occur even if the initial care was timely and appropriate. Whereas early recognition of acute fractures allows for nonoperative management, nonunions frequently require surgical treatment. Traditionally, this has involved open debridement and bone grafting. However, some publications suggest that certain stable nonunions may be amenable to percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…For a scaphoid fracture, primary bone healing depends on rigid stabilization of the fracture fragments. The treatment rationale for fixation without grafting is that instability is the main factor disturbing the healing process and that the stability provided by screws results in healing of minimally displaced fractures (Capo et al., 2009; Ernst et al., 2018; Slade et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a scaphoid fracture, primary bone healing depends on rigid stabilization of the fracture fragments. The treatment rationale for fixation without grafting is that instability is the main factor disturbing the healing process and that the stability provided by screws results in healing of minimally displaced fractures (Capo et al., 2009; Ernst et al., 2018; Slade et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection is important. Although Mahmoud and Koptan (2011) claimed that some scaphoid nonunions with gaps of more than 5 mm could be treated with fixation without grafting, most hand surgeons still believe that scaphoid nonunions with substantial bone loss or sclerosis should be treated by open reduction, bone grafting and internal fixation (Ernst et al., 2018). Poor vascularity of the proximal pole may be an important cause of poor success of the fixation without grafting (Capo et al., 2012; Hegazy, 2015; Somerson et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The exact definition and classification of a fracture as a nonunion is controversial. 28,29 Currently, there is no universally accepted time of continued lack of bony healing that defines a nonunion as compared with a delayed union or nascent nonunion. Several authors have defined scaphoid nonunions as fractures that have not demonstrated bony healing at least 6 months postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have defined scaphoid nonunions as fractures that have not demonstrated bony healing at least 6 months postinjury. 30 Some also define scaphoid fractures that have no evidence of healing at 3 months from injury as nonunions, 28,31 whereas others consider these to be nascent nonunions. 10,31 Conventional treatment of scaphoid nonunions includes screw fixation with nonvascularized bone graft or excision of the proximal pole fragment.…”
Section: Discussionmentioning
confidence: 99%
“…improving understanding of scaphoid vascularity, immobilization strategies, and fixation methods, the optimal strategy for the management of scaphoid fractures continues to be elusive. 1,[11][12][13][14][15][16][17] Operative reduction and internal fixation of scaphoid fractures are indicated for displaced or unstable fractures, delayed fracture presentation, proximal pole fractures, open fractures, and established nonunions. 18,19 Multiple fixation strategies have been described for scaphoid fractures including headless compression screws (HCS), plates, staples, and Kirschner wires (K-wires).…”
mentioning
confidence: 99%